Enhancing sunflower microgreen yield and quality through foliar application of various nutrient solutions - Sirinupong, Manoon; Bourchookarn, Apichai; Htwe, Nang Myint Phyu Sin; Sae-Ong, Mile; Ruangrak, Eaknarin (Agriculture and Natural Resources, 2024)
Importance of the work: Sunflower microgreen production commonly involves the use of growing media without an initial nutrition input, leading to lower yields and compromised quality. Objectives: To enhance the sunflower microgreen yield and quality based on the foliar application of various nutrient solutions and a hydroponic solution with additional nutrient. Materials & Methods: Foliar nutrient solutions, namely hydroponic nutrient solution (HNS), HNS + ammonium sulfate (HNS-AS), HNS + urea (HNS-U), HNS + monosodium glutamate (HNS-MSG) and distilled water (DW) were tested on sunflower microgreens based on a completely randomized design with three replications. The yield and quality parameters of the sunflower microgreens were measured. Results: The HNS-U treatment induced the highest fresh weight, while the dry weight and water contents were not significantly different among the treatments. The HNS-AS treatment had the highest contents of chlorophyll a and carotenoids, while the HNS-MSG treatment had the highest contents of chlorophyll b and total chlorophylls. The DW treatment produced the highest ratios of chlorophyll a to b and chlorophyll a to total chlorophyll, the HNS treatment promoted the highest ratios of chlorophyll a to carotenoid and total chlorophyll to carotenoid and the HMS-MSG treatment stimulated the highest ratios of chlorophyll b to total chlorophyll and chlorophyll b to carotenoid. The protein and ammonium contents of the sunflower microgreens were highest in the HNS-MSG treatment. The sunflower microgreens treated with HNS had the highest nitrate content. However, nitrite levels were not affected by the different foliar applications. Furthermore, the sunflower microgreens treated with HNS-MSG contained four detectable amino acids: cysteine, phenylalanine, tyrosine and tryptophan. Main finding: The foliar application of HNS-MSG and HNS-U showed potential for enhancing the yield and quality of sunflower microgreens.